A report on Sipyloidea stigmata Redtenbacher (Diapheromeridae: Necrosciinae) as the first phasmid crop pest in India and its redescription - Prathapan, K. D.; Anith, K. N.; Faizal, M. H.; Lekha, M.; Dhanya, M. K. (Zootaxa, 2008)
The order Phasmatodea, the stick and leaf insects, include fewer crop pests than other phytophagous groups of insects. Bedford (1978) reviewed their biology and ecology. Outbreaks of stick insects on economically important plants are known from the USA (Graham, 1937), Fiji and other islands in the South Pacific (O’Connor, 1949; Paine, 1968), Australia (Key, 1991) and China (Hennemann, et. al., 2008). Lit and Eusebio (2008) described Pharnacia magdiwang (Phasmatidae) [a junior synonym of P. ponderosa Stål (Hennemann and Conle, 2008)], a minor pest on mango in the Philippines and listed eight species of stick insects associated with economically important plants. Phasmatodea of the Indian subcontinent are poorly known in spite of the rich diversity and none of them are known to be associated with crop plants.